Perancangan Desain Karakter Pada Buku Interaktif Satelit Bulan Untuk Anak Kelas 6 Sekolah Dasar - Sa'diyah, Kholifatus; Sutejo, Aris; Daniar, Aninditya (Metta : Jurnal Ilmu Multidisiplin, 2024)
Learning about outer space, particularly satellites, is an important part of basic education that can foster motivation, curiosity, and interest in exploration among students. In the Semester Learning Plan (RPS) for Thematic Grade 6 Theme 8, the topic of the moon's satellite is often taught. However, this learning is often ineffective due to less creative teachers and inadequate learning media. Therefore, more engaging media is needed to increase student enthusiasm and understanding. This paper focuses on character design in the development of interactive book media about satellites for 6th-grade elementary school students. The method used is qualitative with qualitative descriptive analysis techniques. Primary data were obtained from interviews and observations, while secondary data were obtained from books and journals. The illustration design process includes determining the characteristics of each character, building character concepts, collecting references, determining design concepts, creating design alternatives, evaluating designs, and finalizing designs. Verbal and visual concepts are tailored to the target audience. The results of this design show that attractive interactive book media can enhance the understanding and interest of 6th-grade students in learning about outer space.